Start Making Sense: A Legislator Looks at Professional Licensure Reform - McCormick, Dale (Maine Policy Review, 1996)
This past summer, the Maine Health Professions Regulation Project and its task force released a report to Governor King and the Maine legislature. The report, "Toward a More Rational State Licensure System for Maine’s Health Professions," represents the best thinking and accomplishments of a nearly two-year project directed by Judy Kany of Medical Care Development, Inc. Dale McCormick’s commentary addresses five aspects of this project: the approach of the task force, why licensure reform is necessary, the relationship between this project and the Maine Health Care Reform Commission, the report issued by the task force, and a brief review of the nine "problem areas" and 12 recommendations contained in the report.